Effect of family socioeconomic status on the prognosis of complex congenital heart disease in children: an observational cohort study from China. (June 2018) - Xiang, Li; Su, Zhanhao; Liu, Yiwei; Zhang, Xiaoling; Li, Shoujun; Hu, Shengshou; Zhang, Hao
Summary: Background: Low socioeconomic status is associated with increased mortality for patients with cardiovascular disease; however, the effect of family socioeconomic status on the prognosis of children with congenital heart disease remains unclear, particularly in low-income and middle-income countries. We aimed to examine the association between family socioeconomic status and postoperative outcomes for paediatric patients with complex congenital heart disease (CCHD). Methods: In this observational cohort study, we enrolled children (aged <7 years) who had CCHD surgery at Fuwai Hospital (Beijing, China) between May 1, 2012, and Dec 31, 2015. Patients who were discharged alive were followed up for up to 60 months, until May 4, 2017, for all-cause mortality and unplanned readmission events. Baseline family socioeconomic status was established using a composite of household income in the past year, and occupation and education level of each parent in the family. Cox proportional hazards regression was used to evaluate the relationship between socioeconomic status and prognosis. Findings: Of 2555 patients (median age at operation 0·88 years, IQR 0·56–1·92) enrolled, 2485 (97%) were discharged alive and were assessed at a median follow-up of 32·1 months (IQR 19·6–44·7). During follow-up, 180 (7%) patients died, and 748 (30%) patients had 1477 unplanned readmissions. Children with low family socioeconomic status (n=899) had higher unadjusted all-cause mortality and more unplanned readmission events than children with middle (n=819) or high (n=767) family socioeconomic status; 3-year overall survival was 88·5% (95% CI 86·3–90·7), 93·1% (91·1–95·1), and 96·3% (94·7–97·9), and 3-year unplanned-readmission-free survival was 56·3% (52·8–59·8), 68·4% (64·9–71·9), and 82·4% (79·5–85·3) across the socioeconomic tertiles (both log-rank p<0·001). After adjustment for demographic factors, weight, cardiac diagnostic categories, operation types, and characteristics of the index hospital stay, hazard ratios were 2·66 (1·62–4·35) for all-cause mortality and 4·17 (3·31–5·25) for unplanned readmission for low versus high family socioeconomic status, and 1·95 (1·18–3·22) and 2·44 (1·94–3·07), respectively, for middle versus high family socioeconomic status. Interpretation: Low and middle family socioeconomic status is associated with worse prognosis after CCHD surgery than high family socioeconomic status. Measures to alleviate socioeconomic disparities are needed to improve postoperative prognosis of paediatric patients with CCHD in China. Funding: National Science Fund for Distinguished Young Scholars and National Key R&D Program of China.